Intra-Articular Cytokine Levels in Adolescent Patients after Anterior Cruciate Ligament Tear. (28th August 2018) - Bigoni, Marco; Turati, Marco; Zatti, Giovanni; Gandolla, Marta; Sacerdote, Paola; Piatti, Massimiliano; Castelnuovo, Alberto; Rigamonti, Luca; Munegato, Daniele; Franchi, Silvia; Portinaro, Nicola; Pedrocchi, Alessandra; et al.
Abstract : The treatment of anterior cruciate ligament (ACL) injuries in children and adolescents is challenging. Preclinical and clinical studies investigated ACL repairing techniques in skeletally immature subjects. However, intra-articular bioenvironment following ACL tear has not yet been defined in skeletally immature patients. The aim of this study was to measure cytokine concentrations in the synovial fluid in adolescent population. Synovial levels of IL-1 β, IL-1ra, IL-6, IL-8, IL-10, and TNF- α were measured in 17 adolescent patients (15 boys) with ACL tears who underwent ACL reconstruction including acute (5), subacute (7), and chronic (5) phases. Femoral growth plates were classified as "open" in three patients, "closing" in eight, and "closed" in six. Eleven patients presented an ACL tear associated with a meniscal tear. The mean Tegner and Lysholm scores (m e a n ± S D ) of all patients were 8 ± 1 and 50.76 ± 26, respectively. IL-8, TNF- α, and IL-1 β levels were significantly greater in patients with "open" physes. IL-1ra and IL-1 β levels were significantly higher in patients with ACL tear associated with a meniscal tear. Poor Lysholm scores were associated with elevated IL-6 and IL-10 levels. IL-10 levels positively correlated with IL-6 and IL-8 levels, whereas TNF- α concentration negatively correlated with IL-6 levels. Skeletally immature patients with meniscal tears and open growth plates have a characteristic cytokine profile with particularly elevated levels of proinflammatory cytokines including IL-8, TNF- α, and IL-1 β . This picture suggests that the ACL tear could promote an intra-articular catabolic response in adolescent patients greater than that generally reported for adult subjects. The study lacks the comparison with synovial samples from healthy skeletally immature knees due to ethical reasons. Overall, these data contribute to a better knowledge of adolescent intra-articular bioenvironment following ACL injuries.